Recent developments on recycling end-of-life flat panel displays: A comprehensive review focused on indium. Issue 5 (4th March 2021) - Fontana, D.; Forte, F.; Pietrantonio, M.; Pucciarmati, S.
Abstract: In this paper, a review of the most recent technologies for indium recovery from waste flat panel displays is provided. Differently from the other fractions obtained after primary dismantling (such as plastic casings, printed circuit boards, metallic fractions and the fluorescent lamps) which have assessed recycling routes, the indium-containing panels are currently not properly treated and indium recovery from this residual fraction at industrial scale is still a challenge. Indium has been included in a list of "critical raw materials" by the European Commission and its recovery from secondary sources is gaining increasing attention among the scientific community. Its recovery is mostly performed at laboratory scale via pyro- and hydrometallurgical techniques and a very few examples of pilot-plant solutions can be found in the available literature. FPDs represent a source of valuable materials: besides indium, they contain glass and the polarizing films, which recovery could lead to both economic and environmental advantages. Suggestions for improvement are here provided to close the loop of flat panel displays recycling, in accordance with the principles of Circular Economy. Graphical Abstract: